Cadophora malorum Cs‐8‐1 as a new fungal strain producing gibberellins isolated from Calystegia soldanella. (7th September 2012) - You, Young‐Hyun; Yoon, Hyeokjun; Kang, Sang‐Mo; Woo, Ju‐Ri; Choo, Yeon‐Sik; Lee, In‐Jung; Shin, Jae‐Ho; Kim, Jong‐Guk
<x xml:space="preserve">Abstract</x> Fourteen endophytic fungi with different colony morphologies were isolated from the roots of Calystegia soldanella. Endophytic fungi isolated from C. soldanella were identified by internal transcribed spacer (ITS) region. To verify plant growth promotion (PGP), culture filtrates of isolated endophytic fungi were treated in Waito‐c rice (WR) and C. soldanella seedlings. Culture filtrates of Cs‐8‐1 fungal strain had advanced PGP activity. The presence of physiologically bioactive gibberellins (GA) GA1 (1.213 ng ml−1), GA3 (1.292 ng ml−1), GA4 (3.6 ng ml−1), GA7 (1.328 ng ml−1), other inactive GA9 (0.796 ng ml−1) and GA12 (0.417 ng ml−1), GA20 (0.302 ng ml−1), GA24 (1.351 ng ml−1), GA34 (0.076 ng ml−1), and GA53 (0.051 ng ml−1) in culture filtrates of Cs‐8‐1 fungal strain was detected. The Cs‐8‐1 fungal strain was confirmed as a producer of GAs. Molecular analysis of sequences showed high similarity of 99% to Cadophora malorum. Consequentially, the Cs‐8‐1 fungal strain was identified as a new C. malorum producing GAs.